Prevalence maxillofacial injuries and traumatic dental injuries in Malaysian children and adolescents: a systematic review and meta-analysis - Hisham, Abdul Rauf Badrul; Lin, Galvin Sim Siang; Chua, Hock S.; Ngademan, Ainur U.K.; Bahiar, Ahmad S.S. (Wolters Kluwer Health, 2025)
Aim: This systematic review was undertaken to determine the prevalence of maxillofacial injuries (MFIs) and traumatic dental injuries (TDIs) among children and adolescents in Malaysia.